Humanities and Social Sciences : A Multidisciplinary Approach - Aparna Sharma; Anil Sehrawat; Tapan Kumar Chandola (Routledge, 2026)
This compilation of original, peer-reviewed papers takes a multidisciplinary approach to address a diverse range of topics in the humanities and social sciences. It explores traditional knowledge systems and their relevance to sustainable development, leadership, health, and ethics.The book delves into various themes of Indian Knowledge System, Global Relations, Governance, Policy, and Political Dynamics, Geographical Innovations, Revisiting Indian History and Culture, Contemporary Sociological Imagination, Dialogues in Literature and Literary Discourse, Communication and Language Studies, Contemporary Issues in Mental Health and Well-being, Law, Gender, Human Rights and Teacher Education. With a special emphasis on historical and cultural developments, it provides a comprehensive understanding of society, economy, human behaviour and policy in the modern world through novel academic perspectives.This volume serves as a valuable resource for academicians, researchers and students in the field of humanities and social sciences. It also addresses concerns of policymakers, educators, civil society members, and professionals working in NGOs, governance, law, business, media, and environmental advocacy.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC BY-NC-ND)] 4.0 license.